“Selección de los animales en base a los caracteres de importancia económica en la producción de leche de Bovinosacorde al objetivo de mejora genética en la parroquia Juan Montalvo” - Narváez Castro, Anderson Wilman (2023)
This research was carried out in Cotopaxi province, Latacunga canton, Juan Montalvo parish, from October to January 2023, with the purpose to select parents with good characteristics for future generations. The methodology was descriptive, with direct observation of each cattle farm with a total of 121 studied animals. Data was obtained onmilk production, with cow producing the most (17.2 kg/day), and by herd a median of (8.2 kg/day). In terms of longevity, the minimum age is (2.73) years up to cows with (11.45) years of age. The daily weight gain ¨GDPD¨ a maximum value of 2111 gr/day, with an average of 226 gr/day, and a minimum of - 2946gr/day with an average of 162 gr/day. Milk density values were found to have a maximum density of 29.1 and a minimum of 26 with an average of 27.7. And for Californian Mastitis Test ¨CMT¨ with avalue of (20.5%) for positive samples and (79.5%) in negative tests. Two cows were selected to disseminate their genetic material; Manuela with an average milk production of (10.46 kg/day) and GDP (1216 gr/day) and Fortuna with an average milk production of (15.06 kg/day) and a GDP (759 gr/day), in longevity the two cows exceed 7 years.